Pembentukan Standardisasi dan Konstruksi Kecantikan Perempuan Oleh Akun UNEJ Cantik - Vionata Gadis Ranika; Silvi Cahyaning Kamalia; Desi Tri Wijayanti (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
The development of information and communication technology brings changes to Indonesian society, especially social media. The existence of a beautiful campus account is a digital media that continues to grow and has many followers. This account displays a series of photos of beautiful female students with various beauty standards and demands in them. The more this account develops, the more it will shape the construction of beauty in society. However, behind that there are admins who get profits in the form of royalties from the endorsements that come in through the account. Therefore, this sensitive issue creates pros and cons among students because it is considered a form of business that is carried out by taking advantage of beautiful women. The purpose of this research is to find out the construction of beauty that exists in society and their definition of beauty. This research uses a qualitative method with a phenomenological approach. The research results show various responses regarding beautiful campus accounts and viewing beauty as an objective things.